Inside Cover: Hydrophilic trans‐Cyclooctenylated Noncanonical Amino Acids for Fast Intracellular Protein Labeling (ChemBioChem 16/2016). (2nd August 2016) - Kozma, Eszter; Nikić, Ivana; Varga, Balázs R.; Aramburu, Iker Valle; Kang, Jun Hee; Fackler, Oliver T.; Lemke, Edward A.; Kele, Péter
Abstract : The inside cover picture shows that a new, hydrophilic "amphibian" trans ‐cyclooctene (TCO)‐modified noncanonical amino acid (ncAA) can easily be washed out of cells following site‐specific genetic encoding into the protein of interest. The fluorescent labeling of genetically bio‐orthogonalized intracellular proteins is usually compromised by high background caused by inefficient clearance of existing, more‐hydrophobic TCO‐ncAAs. Typically this was compensated for by extensive washout protocols to remove excess ncAAs from the cellular interior. The presented, easily removable hydrophilic TCO‐ncAA, however, permits fast bio‐orthogonal labeling with very low background signals and paves the way towards studying intracellular proteins that turn over rapidly. More information can be found in the full paper by E. A. Lemke, P. Kele et al. onpage 1518 in Issue 16, 2016 (DOI:10.1002/cbic.201600284 ).